2016
DOI: 10.1111/acer.13255
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Access to Reward Are Associated with College Student Alcohol Use Disorder

Abstract: Background Reward deprivation has been implicated in major depressive disorder and severe substance abuse, but its potential relation to alcohol use disorder (AUD) symptoms in non-treatment seeking young adult drinkers is less clear. Depression is often comorbid with alcohol misuse, so relations of AUD with reward deprivation might be due in part to the presence of depressive symptoms in young adults. Behavioral economic theory views addiction as a state that is related in part to deficits in drug-free rewards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 56 publications
8
32
0
1
Order By: Relevance
“…The RPI includes subscales measuring both access to environmental reward and the ability to experience reward. Joyner and colleagues (2016) found that access to environmental reward , but not the ability to experience reward, predicted a greater risk for alcohol use disorder and alcohol-related problems among college student heavy drinkers. The authors suggest that those with diminished access to environmental reward may have poor access to recreational and educational resources due to poverty, and in some cases, may lack the social skills or self-regulatory capacity to engage in or to take advantage of opportunities to participate in rewarding social, leisure, or academic/community activities.…”
mentioning
confidence: 89%
“…The RPI includes subscales measuring both access to environmental reward and the ability to experience reward. Joyner and colleagues (2016) found that access to environmental reward , but not the ability to experience reward, predicted a greater risk for alcohol use disorder and alcohol-related problems among college student heavy drinkers. The authors suggest that those with diminished access to environmental reward may have poor access to recreational and educational resources due to poverty, and in some cases, may lack the social skills or self-regulatory capacity to engage in or to take advantage of opportunities to participate in rewarding social, leisure, or academic/community activities.…”
mentioning
confidence: 89%
“…A key advance in behavioral economics is research testing whether the rewarding or motivational properties of alcohol may exceed that of most available drug-free rewards among individuals who misuse alcohol, leading to increasing relative valuation of alcohol (Vuchinich & Heather, 2003). A recent study with college student heavy drinkers found that AUD symptoms were uniquely associated with diminished environmental reward availability above and beyond drinking level and depression, but that ability to experience reward was intact (Joyner et al, 2016). Other research suggests that chronic alcohol and other drug use may also lead to a diminished capacity to experience natural reward.…”
Section: Advances In Behavioral Economic Approaches To Understanding mentioning
confidence: 99%
“…Often, reinforcer pathology occurs in the context of diminished reinforcement from alternative activities, resulting in a greater valuation of the addictive behavior relative to available alternative activities. Thus, those with a diminished availability of alternative reward in their environment (reward deprivation) will report greater levels of addictive behaviors (Joyner et al, 2016; Vuchinich & Tucker, 1988). Research with substance-related addictions supports this, showing that greater alcohol use is related to greater levels of substance-related reinforcement relative to substance-free reinforcement (Correia, Carey, Simons, & Borsari, 2003; Joyner, Acuff, Meshesha, Patrick, & Murphy, 2018).…”
Section: Behavioral Economicsmentioning
confidence: 99%